Post-Cretaceous bursts of evolution along the benthic-pelagic axis in marine fishes. Issue 1893 (19th December 2018) - Ribeiro, Emanuell; Davis, Aaron M.; Rivero-Vega, Rafael A.; Ortí, Guillermo; Betancur-R, Ricardo
Abstract : Ecological opportunity arising in the aftermath of mass extinction events is thought to be a powerful driver of evolutionary radiations. Here, we assessed how the wake of the Cretaceous–Palaeogene (K-Pg) mass extinction shaped diversification dynamics in a clade of mostly marine fishes (Carangaria), which comprises a disparate array of benthic and pelagic dwellers including some of the most astonishing fish forms (e.g. flatfishes, billfishes, remoras, archerfishes). Analyses of lineage diversification show time-heterogeneous rates of lineage diversification in carangarians, with highest rates reached during the Palaeocene. Likewise, a remarkable proportion of Carangaria's morphological variation originated early in the history of the group and in tandem with a marked incidence of habitat shifts. Taken together, these results suggest that all major lineages and body plans in Carangaria originated in an early burst shortly after the K-Pg mass extinction, which ultimately allowed the occupation of newly released niches along the benthic-pelagic habitat axis.